Reflecting on Five Decades of Teacher Professional Development in Tanzania: The Missing Dimensions - Dachi, Hillary (Papers in Education and Development, 2016)
The importance of teacher development need not be over stated. This is adducible by the fact that transformations, innovations and diffusions in education make it imperative that teachers have to continually change and adopt. This paper takes stock of the trajectory of teacher professional development in Tanzania by locating related initiatives in the macro-policies and education transformations spanning a period of nearly five decades. It identifies the missing dimensions for robust in-service continuous professional development programmes (CPD) for primary and secondary school teachers. The paper proposes the need to support a cost effective in-service CPD model, which is school based designed around a reflective practitioner approach, for which teaching is an interactive problem solving professional undertaking requiring continuous updating of key competences that teachers require for classroom practices. Key words: teachers ' professionalism; teachers ' continuous professional development; macro-policies; education transformations